Negotiating Indonesian Cultural Identity in Arabic Subtitle Translation of Dear David - Waviq Alfiana Irianti; Sajarwa (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Salatiga, 2025)
Cultural translation in film is a process of negotiation aimed at balancing the accuracy of the source culture with acceptability in the target culture. This study examines how Indonesian cultural identity is negotiated in the subtitle translation of the film Dear David from Indonesian into Arabic. The research employs a qualitative descriptive method with a comparative and interpretative approach. The analyzed data consist of linguistic units, such as words and phrases, that convey Indonesian cultural meanings and their equivalents in the Arabic subtitles. The data source is the film